PĂCATUL – OFENSĂ LA ADRESA LIBERTĂȚII ȘI DEMNITĂȚII CREȘTINE (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Sin – An Offence to Christian Freedom and DignityIf the universality of salvation and righteousness is at the core of the Pauline apostolic sermon, sin represents the negative side of the Pauline discourse. In ancient times, the notion of sin referred to transgressing a social norm of coexistence that is a violation of social conventions (with an external meaning). On the other hand, the Old Testament defines sin as a religious or moral transgression. Thus, it either indicates a rebellion against God, against the order he has established, against his Law, either refers to intentional evil deeds, understood as transgressions or errors from ignorance.